Analisis Kuat Tekan Beton dengan Variasi Agregat Kasar Dicuci dan Tidak Dicuci - Maulana, Jaka Aldian; Jamaludin, Jamaludin; Dewantoro, Fajar (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of washed coarse aggregate and unwashed coarse aggregate on the compressive strength of concrete. In this research, the method used was making concrete test objects in the laboratory of the Indonesian Technocrat University. This research was carried out on 8 cylindrical test objects measuring 15 x 30 cm. Of the 8 test objects made, 4 test objects used washed coarse aggregate and 4 test objects used unwashed coarse aggregate. The tests carried out were concrete compressive strength tests at concrete ages of 7, 14, 21 days. The results of the compressive strength of concrete with washed coarse aggregate, the results of conversion calculations for 28 consecutive days were 244.76 Kg/cm2, 212.19 Kg/cm2, 249.88 Kg/cm2, and 226.99 Kg/cm2. The results of the compressive strength of concrete with aggregate rough unwashed, the results of conversion calculations for 28 consecutive days were 229.64 Kg/cm2, 176.27 Kg/cm2, 179.05 Kg/cm2, and 185.86 Kg/cm2. Based on data from research that has been carried out, it can be seen that concrete that uses washed coarse aggregate material has a stronger compressive strength than concrete that uses unwashed coarse aggregate.